Contributions of Views of Patients and Employees to the Service Improvement, Innovation and Corporate Entrepreneurship: An Instance of a Hospital - , Aykut Ekiyor; , Fadime Basturk (Archives of Current Research International, 2016)
Recently, it has been focused on how to increase organizational development and entrepreneurship in order to ensure the development in the country. The first thing to do on the issue is to determine what innovations can be made to improve the organization. At this point, the contribution provided by the employees and patients of an organization is considerable. The aim of this research is to uncover the contribution of patients’ and employees’ views on the improvement of service, generation of innovation and corporate entrepreneurship. In this context, it is aimed to shed light for hospital managers on the idea of ​​finding resources to provide organizational development and renewal. A likert-type questionnaire appropriate to the purpose of the research study was applied to the hospital staff and the results were evaluated with the patients’ views transmitted to the hospital in the last five months. It was reached to the conclusion that the views of patients and employees contribute significantly on the organizational development, attaching importance to their views enhance the positive contribution and the system should be designed as to increase the value of entrepreneurship by receiving feedback.